Agricultural Programme and National Development in Nigeria: Assessing the Impact of the Anchor Borrowers Programme - Olayinka, Iseoluwa Raphael; Ayodeji, Gafar Idowu; Yusuf, Ibrahim Oladayo; Taiwo, Abayomi Samuel; Sokunbi, Adepeju Rebecca; Olatoye, Oludare Adeolu (UUM PRESS, 2024)
The Anchor Borrower Programme (ABP) was introduced in 2015 by the Federal Government of Nigeria to provide loans for farmers, create jobs, increase agricultural productivity, and create employment to ensure national development. The study employed ordinary least squares regression analysis to examine the program’s impact on national development. The explanatory variables considered include employment in agriculture, food export bill, and food import bill, while the dependent variable is gross domestic product (GDP). The findings revealed that the Food Import Bill, which was 0.2694 (27%) before the program, reduced to 0.0102 (1.02) after the program. Also, the country’s food export bill, which was 0.2884 (28%) before the program, was reduced to (1.7). In contrast, employment in agriculture, which was -0.0534 (-5.3) before the program, further deteriorated to -0.8200 (-82%) after the anchor borrowers’ program. This implies that the anchor borrow program failed to meet the desired expectations. Other findings of the study identified late disbursement of loans to non-farmers, disbursement of funds during off-farming seasons, ineffective loan recovery mechanisms, diversion of loans for non-agricultural purposes, insecurity challenges, and climatic conditions as some of the factors that militate against the efficacy of the program. The paper, therefore, recommends the inclusion of community leaders in identifying agricultural practitioners for loan disbursement and recovery, prompt disbursement of funds, the supply of farm equipment and seedlings rather than cash, and the inclusion of insurance coverage to mitigate the effects of other risks associated with insecurity and climatic trajectories.